Free will, transworld depravity, and divine omniscience - Fiorello, Alessandro (International journal for philosophy of religion, 2025)
In this essay I am going to attempt to resuscitate the logical problem of evil. Since the problem is well known I will be brief in motivating it. It is widely held within the field of philosophy of religion that the problem of evil in its logical form is a dead end. That is, it is accepted that there is no logical incoherence in supposing that a perfectly loving and all-powerful god exists alongside the existence of evil. One of the accepted arguments for the dissolvement of this issue is Alvin Plantinga’s Free Will Defence. I believe that Plantinga’s defence is not the successful argument that scholars in the field have taken it to be. I attempt a demonstration of an inner conflict in Plantinga’s argument that thoroughly undermines the strength of his argument. I show that Plantinga’s argument attempts to smuggle in the possibility of middle knowledge through his concept of transworld depravity. The conclusion of my argument is that Plantinga’s status as solving the logical problem is not warranted and it should be given serious attention.